The pathogenic role of circulating Hashimoto's Thyroiditis‐derived TPO‐positive IgG on fetal loss in naïve mice. (20th September 2020) - Borodina, Elena; Katz, Itai; Antonelli, Alessandro; Gzgzyan, Alexander M.; Dzhemlikhanova, Liailia Kh; Ostrinski, Yuri; Niauri, Dariko; Khizroeva, Jamilya; Bitsadze, Victoria; Makatsariya, Alexander; Tincani, Angela; Nalli, Cecilia; et al.
Abstract: Problem: Antibody‐mediated autoimmune diseases, such as autoimmune thyroid diseases (ATD), systemic lupus erythematosus (SLE), and antiphospholipid syndrome (APS), often are associated with recurrent fetal loss. One of the ATD is Hashimoto's thyroiditis which recently showed association with complications of pregnancy with increased levels of circulating autoantibodies reactive with epitopes on thyroid tissue such as thyroid peroxidase (anti‐TPO). In retrospective study of sera analyses in patients with Hashimoto's thyroiditis, all patients had mainly elevated circulating anti‐TPO autoantibodies. Aim: We assessed the potential of human anti‐TPO highly positive IgG, derived from patients with Hashimoto's thyroiditis sera associated with complications of pregnancy, to cause directly complications of pregnancy in murine model. Method of study: Naïve ICR female mice, infused intravenously with 100 μg of anti‐TPO‐positive IgG, showed increased fetal loss and embryo small for date ( P  < .001) in comparison with mice passively transferred with commercial IgG or PBS. Moreover, we observed embryos small for date in the mice passively transferred with anti‐TPO‐positive IgG, exemplified by reduced weight of embryos and placentae ( P  = .001). Histopathological examination revealed delay in fetal development in 50% cases of anti‐TPO‐positive IgG‐treated mice. Importantly, pathological changes in the transition zone, state of glycogen cells, and significant structural changes in the labyrinth part of placenta were observed in all anti‐TPO‐positive IgG samples. Conclusion: The current study shows in the first time, a direct proof of concept, on the association of human TPO‐positive IgG from Hashimoto's thyroiditis patients on fetal loss induction in murine model.